Multilingual Heritage Tourism Promotion: A Hybrid Printed- Digital Model at an Indonesian Karst Museum - Ariesta Ersidyan; Hajar Adhayanti1; Zhibin Yi; Song Cheng Xian (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study examines the role of Mandarin Chinese-language promotional brochures in enhancing information accessibility for Chinese-speaking visitors and supporting international heritage tourism development at the Indonesia Karst Museum, Wonogiri, Central Java, Indonesia. Methodology: A qualitative single case study design was employed, utilizing semi-structured interviews with 12 purposively selected participants, structured site observation, documentary analysis, and a five-dimension brochure evaluation rubric. Data were analyzed using Braun and Clarke's six-phase reflexive thematic analysis with NVivo 14. Main Findings: Chinese-language brochures improved tourism information accessibility for Chinese-speaking visitors and generated documented visit interest. Key challenges included geological terminology translation complexity, limited design capacity, budget constraints, and restricted distribution networks. University–industry collaboration between Sebelas Maret University and DKPPO Wonogiri provided a viable, low-cost mechanism for multilingual promotional capacity development. Novelty/Originality of this study: This study proposes a hybrid printed-digital multilingual promotion model integrating QR code-enabled digital extensions with printed brochures, specifically designed for resource-constrained heritage destinations in developing countries. It introduces a replicable university–industry partnership framework for generating multilingual promotional capacity at under-promoted geological heritage sites.